2022
DOI: 10.3390/nu14132606
|View full text |Cite
|
Sign up to set email alerts
|

Mealtime TV Use Is Associated with Higher Discretionary Food Intakes in Young Australian Children: A Two-Year Prospective Study

Abstract: Background: Mealtime television use has been cross-sectionally associated with suboptimal diets in children. This study aimed to assess the two-year prospective association between baseline mealtime television use and subsequent diets in young children, and identify socioeconomic differences. Methods: Parents reported their child’s television use at meals, and fruit, vegetable, and discretionary food intakes. Multivariable linear and logistic regression analyses assessed the association between baseline mealti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Previous research has identified cross-sectional associations between eating at a table and better dietary and psychosocial outcomes in children ( 43 , 44 ) . Likewise, emerging prospective evidence suggested that the relationship between children’s mealtime TV use and later intakes of discretionary foods differed by mealtime location ( 18 ) . Families were also able to utilise meal location to set screen use boundaries and implement new mealtime expectations, such as ‘no screens at the table’.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has identified cross-sectional associations between eating at a table and better dietary and psychosocial outcomes in children ( 43 , 44 ) . Likewise, emerging prospective evidence suggested that the relationship between children’s mealtime TV use and later intakes of discretionary foods differed by mealtime location ( 18 ) . Families were also able to utilise meal location to set screen use boundaries and implement new mealtime expectations, such as ‘no screens at the table’.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, children from families of lower SEP may be most likely to engage in mealtime screen use (16) . Evidence suggests that mealtime screen use reduces opportunities for family cohesion at mealtimes (17) , and cross-sectional (11) and 2-year prospective evidence (18) suggests that children's diets are poorer when screens are included in family meals. Qualitative research with diverse (19) and low-income (20) families has also found that many parents acknowledge mealtime screen use as not aligning with best practice eating environments and that turning the TV off would improve family communication and connection.…”
mentioning
confidence: 99%